2005
DOI: 10.1242/jeb.01830
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical and morphological properties of different muscle–tendon units in the lower extremity and running mechanics: effect of aging and physical activity

Abstract: SUMMARY The objectives of this work were (i) to investigate whether chronic endurance running is a sufficient stimulus to counteract the age-related changes in the mechanical and morphological properties of human triceps surae(TS) and quadriceps femoris (QF) muscle–tendon units (MTUs) by comparing runners and non-active subjects at different ages (young and old), (ii) to identify adaptational phenomena in running mechanics due to age-related changes in the mechanical and morphological properties… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
105
3
7

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 136 publications
(127 citation statements)
references
References 89 publications
12
105
3
7
Order By: Relevance
“…It is likely that the age-related motor unit remodeling (for review see Andersen. 2003) and changed tendon mechanical properties (Karamanidis and Arampatzis. 2005;Kubo et al 2003;Morse et al 2005) favor different kinds of muscle activation for optimal efficiency and power output in these two age groups (Lichtwark and Wilson.…”
Section: Discussionmentioning
confidence: 99%
“…It is likely that the age-related motor unit remodeling (for review see Andersen. 2003) and changed tendon mechanical properties (Karamanidis and Arampatzis. 2005;Kubo et al 2003;Morse et al 2005) favor different kinds of muscle activation for optimal efficiency and power output in these two age groups (Lichtwark and Wilson.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, it has been observed that lower intensity exercise in the form of a 6-month progressive walking programme does not influence tendon properties in older adults (Kubo et al 2008). In younger habitual distance runners (age <65 years), tendon stiffness is similar to that in non-running controls (Karamanidis and Arampatzis 2005;Rosager et al 2002;Westh et al 2008). Similarly, 6 months of training using body weight squats (50 repetitions (reps) daily) has been reported to have no significant effect on the stiffness of the vastus lateralis tendon (Kubo et al 2003), thereby further indicating the possibility of loading threshold for tendon stiffness increments.…”
Section: Introductionmentioning
confidence: 93%
“…Direct measurements of fiber length of lower limbs muscles have been made by ultrasonic photography in humans [67][68][69][70][71][72][73] and sonomicrometry in animals simultaneous with force measurements using tendon force buckles [21,74]. These studies helped to show the relation between the force-length relation of muscle fibers and the torque-angle relation at the corresponding joint [67,73], and to elucidate the muscle-tendon interaction during the stretch-shorten cycle [69][70][71].…”
Section: Effect Of Running Speed On Landing-takeoff Asymmetry In Adulmentioning
confidence: 99%